Antioxidant Therapies and Oxidative Stress in Friedreich's Ataxia: The Right Path or Just a Diversion? - Laura R. Rodríguez; Tamara Lapeña; Pablo Calap-Quintana; María Dolores Moltó; Pilar Gonzalez-Cabo; Juan Antonio Navarro Langa (MDPI AG, 2020)
Friedreich's ataxia is the commonest autosomal recessive ataxia among population of European descent. Despite the huge advances performed in the last decades, a cure still remains elusive. One of the most studied hallmarks of the disease is the increased production of oxidative stress markers in patients and models. This feature has been the motivation to develop treatments that aim to counteract such boost of free radicals and to enhance the production of antioxidant defenses. In this work, we present and critically review those "antioxidant" drugs that went beyond the disease's models and were approved for its application in clinical trials. The evaluation of these trials highlights some crucial aspects of the FRDA research. On the one hand, the analysis contributes to elucidate whether oxidative stress plays a central role or whether it is only an epiphenomenon. On the other hand, it comments on some limitations in the current trials that complicate the analysis and interpretation of their outcome. We also include some suggestions that will be interesting to implement in future studies and clinical trials.